Identification and expression profiling of LSD genes reveal their role in developmental and abiotic stress conditions in maize - Zhao, Dongbo; Wei, Longxue; Guo, Jianjun; Guo, Zhihui; Guo, Lianghai; Gao, Jiansheng; Cui, Huini; Tai, Rongjian; Guan, Peiyan; Zhang, Liang; Liu, Peng; Jin, Yirong (Frontiers in Plant Science, 2026)
The Lesion Simulating Disease (LSD) genes encode a class of zinc finger proteins that play crucial roles in hypersensitive responses and programmed cell death (PCD) triggered by biotic and abiotic stresses. However, the comprehensive genome-wide identification of the LSD family in maize, comparative synteny analysis, and systematic tissue- and stress-specific expression profiling remain poorly understood. In this study, we systematically identified and characterized the LSD gene family at the genome-wide level in maize. Bioinformatics methods were employed to analyze the physical and chemical properties, chromosomal location, phylogenetic relationships, conserved motifs, and gene structure of the LSD gene family members. The expression patterns of the ZmLSDs under the conditions of drought, high temperature, high salt, and hormone treatment with ABA, were detected by RT-qPCR. The subcellular localization of the ZmLSDs was observed by laser confocal microscopy. A total of nine LSD genes encoding 23 protein isoforms was identified from the maize genome and named ZmLSD1 to ZmLSD9. ZmLSD family proteins have 113–898 amino acids, relative molecular weights ranging from 12.133 to 93.568 KD. The ZmLSD gene family members were distributed on five chromosomes, mainly on Chr1 and Chr3. According to phylogenetic analysis, the ZmLSD family members can be divided into four subfamilies. Motif analysis revealed that Motif1 is the conserved motif shared by these genes, which is presumably related to the conserved structural domain. There were three intra-species covariance gene pairs, and seven ZmLSDs exhibited syntenic homologs with both sorghum and japonica rice LSD genes. ZmLSD3, ZmLSD4, and ZmLSD9, were expressed at higher levels in all tissue sites, except the embryo and endosperm. Expression profiling analysis showed that ZmLSDs can respond to drought, high temperature, high salt, and ABA hormone, especially most of the genes were down-regulated significantly after heat and drought stress treatments, which indicated that ZmLSDs play an important role in coping with abiotic stress in maize. ZmLSD3 was mainly distributed in the cytoplasm, while ZmLSD4 was distributed in both the nucleus and cytoplasm. The above results indicate that the LSD gene family plays an important role in regulating abiotic stress and hormone ABA responses during maize growth and development.